Lenguajes, públicos y apropiación de ciencia escrita - Giraldo Giraldo, Camilo (2016)
The study characterizes the written science to clarify the languages and audiences that deploying and to establish whether such audiences appropriated science through written language. The descriptive method that allowed to specify to specify the components and functions of written communication of science that was used. From this, it was investigated by the written languages (private and open) according to the audiences they target. Then he sought it to determine the appropriation of science in every public. The study showed the tendency to standardization of a written language between specialists. The paper is the document model of such standardization. It was also found a speech decanting for education and other suitable for the general public. The appropriation of science through the writing is possibl in so far as working with written language. In addition, the synonymy between science popularization and science education among science popularization and science journalism was evident erratic. It conclude that science is a matter of written language. The goal of neutrality for the scientific language is maintained, despite criticism by positivists features in which it sits.